Is the Deleterious Effect of Cryotherapy on Proprioception Mitigated by Exercise? - Ribeiro, F.; Moreira, S.; Neto, J.; Oliveira, J. (International Journal of Sports Medicine, 2013)
This study aimed to examine the acute effects of cryotherapy on knee position sense and to determine the time period necessary to normalize joint position sense when exercising after cryotherapy. 12 subjects visited the laboratory twice, once for cryotherapy followed by 30 min of exercise on a cycloergometer and once for cryotherapy followed by 30 min of rest. Sessions were randomly determined and separated by 48 h. Cryotherapy was applied in the form of ice bag, filled with 1 kg of crushed ice, for 20 min. Knee position sense was measured at baseline, after cryotherapy and every 5 min after cryotherapy removal until a total of 30 min. The main effect of cryotherapy was significant showing an increase in absolute (F7,154=43.76, p<0.001) and relative (F7,154=7.97, p<0.001) errors after cryotherapy. The intervention after cryotherapy (rest vs. exercise) revealed a significant main effect only for absolute error (F7,154=4.05, p<0.001), i. e., when subjects exercised after cryotherapy, the proprioceptive acuity reached the baseline values faster (10 min vs. 15 min). Our results indicated that the deleterious effect of cryotherapy on proprioception is mitigated by low intensity exercise, being the time necessary to normalize knee position sense reduced from 15 to 10 min.
Keywords: ice; joint position sense; knee; warm-up exercise